Effects of different drying techniques on the quality and bioactive compounds of plant-based products: a critical review on current trends. Issue 8 (15th June 2022) - Belwal, Tarun; Cravotto, Christian; Prieto, M. A.; Venskutonis, Petras Rimantas; Daglia, Maria; Devkota, Hari Prasad; Baldi, Alessandra; Ezzat, Shahira Mohammed; Gómez-Gómez, Lourdes; Salama, Maha Mahmoud; Campone, Luca; Rastrelli, Luca; et al.
Abstract: Drying is one of the foremost and important steps during the processing of agricultural crops, medicinal plants and herbs to preserve their properties. The present review provides a detailed overview regarding the effect of drying techniques on the physio-chemical properties (microstructure, color, aroma composition) and bioactive compounds (phenolic compounds, carotenoids, essential oils, etc.) of plant materials. Factors affecting different drying processes and their optimization strategies have also been discussed. Furthermore, current trends in the development of drying techniques for plant materials in terms of the retention of their bioactive compounds are critically analyzed. Based on the published research articles, oven drying, and microwave drying are the preferable techniques for most plant parts; while for drying the plant extract, freeze/spray drying methods have gained higher interest. Finally, recommendations are made considering the better use of drying techniques for both plant materials and retention of their bioactive compounds.